The Effectiveness of Elevated-Intensity Interval Exercise compared to Moderate-Intensity Constant Exercise in Increasing Muscle Mass among Obese Women - Candrawati, Susiana; Ilham, Khoerul; Fatchurohmah, Wiwiek (Fakultas Kedokteran Universitas Brawijaya, 2025)
Obesity is associated with muscle function impairments and can progress to functional domain disorders including strength, mobility, and postural balance deficits. Exercise helps with weight management and enhances mass of muscle. Two physical exercise programs available are Elevated-Intensity Interval Exercise and Moderate-Intensity Constant Exercise. Choosing the right type of physical exercise for increasing muscle mass is very important for people with obesity. This study aimed to determine muscle mass changes following physical exercise intervention and compare muscle mass increases in obese women between interval versus constant exercise. The research design was a Randomized Controlled Trial (RCT) with 30 subjects divided into two groups (15 per group) using purposive sampling. Each participant performed cycling-based physical activity using a cycle ergometer for 12 weeks, three times weekly. Muscle mass was measured using Bioelectrical Impedance Analysis (BIA) before and after intervention. Data were analyzed using T-test. Paired T-test results showed significant muscle mass increases in both intervention models (p=0.000). Elevated-intensity interval exercise increased muscle mass by 1.2 ± 0.75, while moderate-intensity constant exercise increased it by 0.98 ± 0.54. Unpaired T-test revealed no significant difference between the two groups' mean muscle mass changes (p=0.341). Both moderate-intensity constant exercise and elevated-intensity interval exercise effectively increase muscle mass in obese women, with both training modalities having equal effectiveness in increasing muscle mass.